Hydrogen Production in Methane Decomposition Reactor Using Solar Thermal Energy - Haneol Kim (MDPI AG, 2021)
This study investigates the decomposition of methane using solar thermal energy as a heat source. Instead of the direct thermal decomposition of the methane at a temperature of 1200 °C or higher, a catalyst coated with carbon black on a metal foam was used to lower the temperature and activation energy required for the reaction, and to increase the yield. To supply solar heat during the reaction, a reactor suitable for a solar concentrating system was developed. In this process, a direct heating type reactor with quartz was initially applied, and a number of problems were identified. An indirect heating type reactor with an insulated cavity and a rotating part was subsequently developed, followed by a thermal barrier coating application. Methane decomposition experiments were conducted in a 40 kW solar furnace at the Korea Institute of Energy Research. Conversion rates of 96.7% and 82.6% were achieved when the methane flow rate was 20 L/min and 40 L/min, respectively.